Using WindTunneling to document emergent knowledge to explore common perceptions of well‐being. - Winn, Karrin (Systems Research & Behavioral Science, 2024)
The purpose of this paper is to discuss using WindTunneling to document emergent knowledge to explore common perceptions of well‐being. WindTunneling is a systemic research methodology to help groups navigate complex issues. In 2022, I adapted WindTunneling to document sensory‐based emergent knowledge from 978 international participants exploring 52 somatic movement activities designed to promote well‐being. Well‐being is a complex subjective condition that is difficult to measure and maintain the richness of diverse perspectives. Discovering common perceptions of well‐being using WindTunneling would partially substantiate the efficacy of movement as a well‐being intervention in context specific situations. If successful, this research design would add to the rigor of WindTunneling as a way to develop a holistic understanding of how participants perceive well‐being in relationship to their lived experience. Developing WindTunneling methodology to meet appropriate qualitative research standards would have practical significance to researchers working to measure the subjective dimension of well‐being.